Performance of Coded Modulation in Multicarrier CDMA System - Linda Meylani; Nur Andini; Iswahyudi Hidayat (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
Coded modulation scheme introduce robust and reliable system. It combine coding and modulation in one system. This paper show performance of coded modulation with coding rate 2/3, using 8PSK and convolutional coding that implemented in MC CDMA system. MC CDMA is one of multicarrier system  that combine OFDM and CDMA so its offer reliable system in frequency selective fading. Decoding process for coded modulation is done by using log likelihood ratio for least significant bit (define the subset) and the entire bits (member of subset). Simulation result shown that coded modulation in MC CDMA system have a good performance in flat fading and frequency selective fading.